Fermentation characteristics of silages made with different proportions of sunflower and Gliricidia sepium added with doses of citric acid - Barbosa, Barbara Venâncio; Van Cleef, Eric Haydt Castello Branco; Galati, Vanessa Cury; Kaneko, Flávio Hiroshi (Revista de Ciências Agroveterinárias, 2025)
The aim on this study was to assess the fermentative characteristics of silages produced with different proportions of sunflower and Gliricidia sepium, supplemented with doses of citric acid. The ensiled material was composed of two crops, sunflower and gliricidia. The experimental design was completely randomized in a 5 × 4 factorial scheme, with five proportions of sunflower and gliricidia (100% sunflower; 75% sunflower and 25% gliricidia; 50% sunflower and 50% gliricidia; 25% sunflower and 75% gliricidia; and 100% gliricidia) and four concentrations of citric acid (0; 0.25; 0.50; 0.75%), with three replications, totaling 60 experimental silos. It was observed that treatments with higher proportions of Gliricidia resulted in lower fermentation capacity and reduced dry matter levels. The pH decreased in treatments with higher proportions of Gliricidia and acid. When analyzing soluble carbohydrate values, higher Gliricidia inclusion demonstrated higher percentages of carbohydrates. The addition of acid showed a linear effect on dry matter losses. Gas production exhibited a quadratic effect for Gliricidia, with the treatment with 75% inclusion showing the lowest production. There was a quadratic effect for acid addition, with the 0.25% acid treatment presenting the highest gas production. Gliricidia inclusion linearly increased gas losses, and the same occurred for citric acid. For ammoniacal nitrogen analysis, a significant quadratic effect (P<0,05) was observed for acid addition, with the highest mean observed in treatments with 0.50% acid. The final pH of silage was linearly influenced by Gliricidia addition (P<0,0001) and linearly for citric acid (P<0,0001). When analyzing CP, no significant differences were observed (P>0,05). It is concluded that the inclusion of Gliricidia sepium in the silage reduces fermentative capacity and dry matter content, while the addition of citric acid linearly influences gas losses and final pH, demonstrating that both factors significantly affect the fermentative characteristics of the silages.